Adaptasi Elong Bugis Dalam Teater Musik Eksperimental: Studi Practice-Based Research Pada Karya Mattajeng - Arjun Subbanul Akbar; Prusdianto Prusdianto (Universitas Negeri Makassar, 2025)
This study aims to examine the adaptation of Bugis Elong into experimental music theatre through the work MATTAJENG as an effort to revitalize oral tradition within the context of contemporary performing arts. As the practice of Elong has gradually declined in Bugis society due to social change and the growing influence of popular culture, creative strategies are needed to ensure that this tradition remains alive, relevant, and accessible to contemporary generations. The study employs a qualitative method using a Practice-Based Research (PBR) approach and a case study strategy, positioning the artistic creation process as the primary medium for knowledge production. Data were collected through literature review, participant observation, audiovisual documentation, cultural discussions, and artistic reflection throughout the creative process. The adaptation process was carried out through the stages of reception, creation, and transposition, which included the reading of Elong Toto Maruddani, vocal and bodily exploration, sound experimentation, and the development of the performance’s musical dramaturgy. The findings reveal that the adaptation of Bugis Elong produced a musical dramaturgical structure consisting of five main phases: initiation, exploration, interaction, ritualization, and resolution. The study demonstrates that the vocal qualities, repetition, and emotional intensity of Elong were preserved, while its musical and dramaturgical structures were transformed into a performative system integrating body, voice, instruments, and performance space. Furthermore, everyday Bugis activities, the Mappadendang tradition, and Makkelong practices were transformed into sound compositions and performative actions that construct experiences of waiting, longing, and collective memory. This study confirms that experimental music theatre can serve as a strategy for cultural revitalization while offering a model for adapting oral traditions into musical dramaturgy within contemporary performance practices rooted in local traditions.